Sexual dimorphism observed in Chionodraco myersi DEWITT and TYLER - Tetsuo Iwami; Tokiharu Abe (National Institute of Polar Research, 1981)
External morphological characters and sexes of Chionodraco myersi which was caught in the Ross Sea were examined. The relative length of the longest dorsal spine to the standard length of fish varied from 9.0% to 30.0% of the standard length. A histological observation revealed that twenty-three female specimens had the lower dorsal fin (9.4%∿16.3% of the standard length) and eight male specimens had the higher dorsal fin (22.5%∿30.0% of the standard length). As the morphological characters of the types of Chionodraco markhami resemble those of the "high dorsal" group, it seems that the species name of Ch. markhami should be given to males of Ch. myersi. The present results support the opinion that Ch. markhami is a synonymy of Ch. myersi.